In vitro growth assessment of Trichoderma spp. from paddy rhizosphere on glyphosate- and fipronil- containing medium - AGNES V. SIMAMORA; PETRONELLA S. NENOTEK; MAYAVIRA V. HAHULY; LILY F. ISHAQ; SRI WIDINUGRAHENI; YENNY RAJA KANA; SPERATUS C. U. PASI; ANTONIUS R. B. OLA; EVERT Y. HOSANG; BAYU R. FITRIADI (Society for Indonesian Biodiversity, 2025)
Abstract. Simamora AV, Nenotek PS, Hahuly MV, Ishaq LF, Widinugraheni S, Kana YR, Pasi SCU, Ola ARB, Hosang EY, Fitriadi BR. 2025. In vitro growth assessment of Trichoderma spp. from paddy rhizosphere on glyphosate- and fipronil- containing medium. Biodiversitas 26: 2028-2038. Agricultural practices worldwide increasingly rely on synthetic pesticides to enhance crop productivity and manage pest infestations. Glyphosate, a widely used herbicide, and fipronil, a broad-spectrum insecticide, are extensively applied due to their effectiveness. However, prolonged use of these agrochemicals raises significant environmental concerns, particularly soil contamination, which disrupts microbial diversity and degrades soil health. The persistence of glyphosate and fipronil in soil ecosystems challenges sustainable agriculture, necessitating the exploration of bioremediation strategies. Research on the ability of Trichoderma spp. to degrade these pesticides remains limited, highlighting the need for this study. This research aimed to (i) isolate Trichoderma spp. from paddy fields with frequent glyphosate and fipronil application; (ii) assess their growth on PDA media supplemented with glyphosate and fipronil; and (iii) evaluate their in vitro potential for pesticide degradation. Growth assessments were conducted on PDA media supplemented with glyphosate at 0 mL/L (control), 5.0 mL/L (recommended concentration), and 12.5 mL/L, and with fipronil at 0 mL/L (control), 2.0 mL/L (recommended concentration), and 4.0 mL/L. The degradation potential was evaluated using a modified dual-culture method with Fusarium oxysporum as the indicator pathogen. The results showed four Trichoderma isolates were obtained, namely T. harzianum 01, T. camerunense 02, T. harzianum 03, and Trichoderma 04. Growth analysis indicated that T. harzianum 01 had the highest colony diameter (9.0 cm) and exhibited complete resistance at recommended glyphosate and fipronil concentrations, while T. camerunense 02 was the most sensitive. Relative inhibition rate analysis confirmed that glyphosate had a stronger inhibitory effect than fipronil. Antagonism tests revealed that all isolates suppressed Fusarium oxysporum, with inhibition rates ranging from 70.59 to 83.96%, indicating strong biocontrol potential. These findings demonstrate the resilience of Trichoderma spp. under pesticide exposure and their capacity to inhibit phytopathogens, supporting their potential as bioremediation and biological control agents for sustainable soil management.